Göğüs Kalp Damar Anestezi ve Yoğun Bakım Derneği Kuruluş ve Tarihçesi (I) - (:unkn) unknown (My University, 2019)
Göğüs Kalp Damar Anestezi ve Yoğun Bakım Derneği 1990 yılında İstanbul’da kurulmuştur. 2019 yılı itibariyle Türkiye genelinde 580 üyesi mevcuttur. Ulusal ve uluslararası alanda düzenlediği kongreler, bölgesel toplantılar, kurs ve çalıştaylar, bilimselyayınlar, diğer ulusal ve uluslararası derneklerle (EACTA, SCA) olan ilişkileri ile bu alanda belirleyici ve öncü çalışmalarını sürdürmektedir. Derneğimizin yıllık ulusal kongreleri, konuların teorik ve pratik yönden hakimi olan yurtiçinden ve dünyanın dört biryanından yabancı konuk konuşmacıların katılımı ile yıllardır devam etmektedir.Uzmanlık sonrası eğitimde önemli olan güncel kurslar, tez-antitez tartışmaları ile anestezinin bu en sofistike dalında emek veren meslekdaşlarımızın deneyimlerinin paylaşıldığı bir ortam oluşturulmaya çalışılmaktadır. Derneğin kuruluşundan bu yana GKDA veYBD Dergisi yayınlanmaktadır. Bu yıl GKDA ve YBD 25. Ulusal Kongresi yapılacaktır. Buderleme ile 29 yıllık derneğin kuruluş ve ilk yılları ile ilgili tarihçe özetlenmeye çalışılmıştır.

The Society of Thoracic and Cardio-Vascular Anesthesia and Intensive Care was founded in 1990 in Istanbul and 580 members by 2019. The Association continues its’ decisive and pioneering role in the field by conducting scientific researchs, organizing national and international congresses, regional meetings, workshops and cooperations with other national and international associations (EACTA, SCA). The annual national congresses of our association have been going on for many years with the participation of foreign guest speakers from all over the world as well as speakers from various centers in the country which are the theoretical and practical masters of the subjects. A creative environment in which the most sophisticated fields of anesthesia shared with up-to-date residency courses and pro-con discussions is targeted. Furhermore The Journal of The Society of Thoracic Cardio-Vascular Anaethesia and Intensive Care has been published since the foundation of the association. This year 25th National Congress will be held. In this review, it is aimed to summarize the history of the establishment and the early years of the 29-years of association.
History of The Society of Thoracic Cardio-Vascular Anaesthesia and Intensive Care (I)
Keywords: Tarih